1992
DOI: 10.1212/wnl.42.11.2082
|View full text |Cite
|
Sign up to set email alerts
|

Acute quadriplegic myopathy

Abstract: We studied two patients who were given high-dose intravenous steroid therapy and were intubated for status asthmaticus. Both became quadriplegic and wasted within 2 weeks. EMG had myopathic abnormalities. Muscle biopsy revealed severe atrophy of most muscle fibers, with disorganization of myofibrils and selective loss of thick (myosin) filaments. Immunohistologic stains for myosin isoforms confirmed the decrease or absence of this protein. Both patients clinically improved over several months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
7

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(89 citation statements)
references
References 12 publications
4
78
0
7
Order By: Relevance
“…In this study the agents more commonly related with myopathy were corticosteroids that can be associated either with acute or chronic myopathy; the latter was more common as had also been reported in other series 1,3,8,9 . This form of myopathy can occur in up to 60% or more of patients in chronic use of corticosteroids 3 .…”
Section: Discussionsupporting
confidence: 73%
“…In this study the agents more commonly related with myopathy were corticosteroids that can be associated either with acute or chronic myopathy; the latter was more common as had also been reported in other series 1,3,8,9 . This form of myopathy can occur in up to 60% or more of patients in chronic use of corticosteroids 3 .…”
Section: Discussionsupporting
confidence: 73%
“…Several other authors, by use of muscle biopsies, confirmed the occurrence of an acute myopathy in the intensive care unit, associated with the use of corticosteroids and neuromuscular blocking agents (37, 141,165,314,382). These patients exhibited preferential myosin loss and also demonstrated flaccid weakness and failure to wean from the respirator.…”
Section: History Time Course and Clinical Features Of Icu-relatmentioning
confidence: 85%
“…Finally, the combination of mechanical ventilation with muscle-relaxing agents and/or high-dose steroids was reported to be associated with significant myopathy [19][20][21][22][23]24]. Muscle weakness varied from mildto-severe.…”
Section: Patient Studiesmentioning
confidence: 99%